Implementation of Budgeting Policies Pandemic Handlingcorona Virus Disease 2019 in Bekasi City - Bambang Heru Purwanto; Iman Sudirman; Hesti Widiastuti (Pasundan Social Science Development, 2022)
Policy implementation in budgeting for handling the COVID-19 pandemic in Bekasi Cityhas not been fully achieved effectively. The Bekasi City Government and its staff have not been optimal in a comprehensive mannerimplement steps to accelerate the handling of COVID-19. This of course will greatly hinder the acceleration of the handling of COVID-19 within the GovernmentBekasi City in handling the fieldhealth, handling economic impacts and provision of a social safety net. The research method used in this research is descriptive analysis with a qualitative case study approach. The results of the research are that there are several factors that cause the implementation of policies in budgeting for handling the COVID-19 pandemic in Bekasi Citynot yet fully effectivenamely communication factors and policy factors so that they can interfere with the acceleration of handling the pandemic in Bekasi City. To make this effective, the Bekasi Mayor ordered the Regional Government Budget Team (TAPD) to immediately make adjustments to the 2020 Regional Revenue and Expenditure Budget (APBD) by refocusing the budget for both income and expenditure and then reallocating the budget in Unexpected Expenditures to be used for accelerated handling the COVID-19 pandemic adequately and increase capacity and coordinate with the Regional Leadership Communication Forum (Forkopimda), community organizations as well as community/religious leaders to socialize and urge the public to avoid the spread of COVID-19. The realization of the implementation of budgeting policies for handling the COVID-19 pandemic in Bekasi Cityeffectively by the Municipal Government of Bekasiincluding support from all parties for policies in budgeting for handling the COVID-19 pandemic in Bekasi City, handling COVID-19 through the policy of implementing the Rukun Warga Siaga program which can be said to be successful and effective, synergy between TAPD and Regional Apparatuses in supporting the commitment of the Mayor of Bekasi City, strengthening coordination and synchronization of policies for handling pandemics between stakeholders and public non-compliance with government appeals from both the Central Government and the Regional Government of Bekasi City can be avoided.